Akumulasi Kalkulus Gigi yang Berlebihan pada Penderita Diabetes Tipe 2: Gejala Klnis Kemungkinan Menderita Penyakit Jantung Koroner - Yulianti Kemal (Journal of Dentistry Indonesia, 2015)
The relaive risk for Coronary Heart Disease (CHD) death in type 2 diabetics was 1.9-3.3 times higher, when compared to non-diabetics. Pathological studies have demonstrated a strong correlation between the presence of coronary calcium and CHD. Previous studies reported that the accumulation of dental plaque and dental calculus, and the severity of periodontal disease in type 2 diabetics were widely varied. A cross-sectional study on periodontal and CHD status of 36 non smoker type 2 diabetics was performed. The periodontal status was determined using Plaque Index of Sillness and Löe, Calculus Index of lingual anterior teeth, Papillary bleeding Index of Muleman, Periodontal Index of Russell, and dental panoramic rontgenogram. The CHD was determined by using standard ECG recording. Statistical analysis was using Fisher's exact test with the significant level of p<0.05. The result of the study showed that a heavy generalized dental plaque accumulation (score>2) was not found in positive CHD diabetics, but found in 925 (36%) of negative CHD diabetics; a slight to moderate dental plaque accumulation was found in 11/11 (100%) of positive CHD diabetics, and 16/25 (64%) of negative CHD diabetics (p=.03). A heavy lingual calculus accumulaiton (score>2) was found in 11/11 (100%) of positive CHD diabetics and 10/25 (40%) of negative CHD diabetics (p=0.006). A severe generalized gingival bleeding (score>2) was not found in positive CHD diabetics, but found in 8/25 (32%) of negative CHD diabetics; a mild to moderate gingival bleeding was found in 11/11 (100%) of positive CHD diabetics and 17/25 (68%) of negative CHD diabetics (p=0.7). A severe generalized periodontal disease (score>5) was not found in positive CHD diabetics, but found in 9/25 (36%) of positive CHD diabetics; a mild to moderate periodontal disease (score<5) was found in 11/11 (100%) of positive CHD diabetics and 16/25 (64%) of negative CHD diabetics (p=.03). In conclusion, our data suggest that in type 2 diabetics, the presence of CHD is significantly correlated with the presence of a slight to moderate dental plaque accumulation, a heavy lingual calculus accumulation of anterior teeth, and a mild to moderate periodontal disease status. Although all the positive CHD diabetics have a mild to moderate gingival bleeding, the CHD status is not significantly correlated with the gingival bleeding status.